Apparent nosocomial adaptation of Enterococcus faecalis predates the modern hospital era - Anna K. Pöntinen (Nature Portfolio, 2021)
Enterococcus faecalis is a commensal microorganism of animals, insects and humans, but also a nosocomial pathogen. Here, the authors analyse genomic sequences from E. faecalis isolates from animals and humans, and find that the last common ancestors of multiple hospital-associated lineages date to the pre-antibiotic era.